Exploring the Potentials of Augmented Reality in Medical Education: A Bibliometric Analysis and Scientific Visualization - Aldira Ayu Nastiti Nur Hanifah; Siti Munawaroh; Nanang Wiyono; Yunia Hastami; Zalik Nuryana; Muthmainah (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2024)
Alongside the COVID-19 pandemic, digitalization has significantly impacted medical education. The pandemic has necessitated several adaptations, including transitioning from a traditional learning model to a digital-based one. One form of this is augmented reality (AR). The future adoption of AR in medical education is bright and considerable. Therefore, evaluating AR in medical education is essential. One such method is bibliometric analysis. Using comprehensive bibliometric analysis, we aimed to collect data on the tendencies of this topic. The research examined terms, countries/territories, publication numbers, institutions, authors, and published journals. The Scopus database was used to compile the material. VOSviewer analyzed the complete bibliometric information. The analysis was based on data from 379 Scopus papers that met our criteria. The statistics demonstrated that the most significant expansion occurred in 2021, with the USA being the most productive country. The Journal of Studies in Health Technology and Informatics is the leading publication, and the Aristotle University of Thessaloniki has published the most papers.